Logistic-type variables that have led companies to locate themselves in the AMCO - Bernal Loaiza, María Elena; Ordoñez Rosero, Diego Fernando; Castañeda Quijano, Roberto (Scientia et Technica, 2019)
The localization of logistic centers contributes to the productivity, development and competitiveness of entrepreneurial organizations; therefore, the aim of this article is to describe the variables of logistic type that allow an organization to set up its operations in the Area Metropolitana Centro Occidente (AMCO). In methodological terms, the first step was to determine the companies that develop their logistic activities with AMCO as their operational center. The second step was to apply a multi-criteria tool to the selected companies. Finally, an instrument of information collection was designed and applied, which permitted the identification and analysis of the variables. The results show that the variables of logistic type are: sales, assets, location, and logistic operation. It is concluded that the companies were placed in the AMCO, profiting from the opportunity to be in a strategic zone of the country, equidistant from Bogotá, Medellin and Cali, and close to the Port of Buenaventura, a zone which lodges about 24 million inhabitants (50% of the total population), where most of the Gross National Product of the country is generated